PEMETAAN PERSEBARAN DAN TINGKAT KERUSAKAN TERUMBU KARANG DI PERAIRAN DESA MAILEPPET KECAMATAN SIBERUT SELATAN - Vincensius Saurei; Novelisa Suryani; Osronita Osronita (Universitas Tamansiswa Padang, 2025)
This research was conducted in the waters of Maileppet Village, South Siberut District. The study aimed to (1) map the distribution of coral reefs and (2) determine the level of coral reef damage in the area. Data processing for mapping the coral reef distribution utilized an unsupervised classification algorithm, specifically Classify Without Training, using ArcMap 10.8 software, while Excel was used to calculate the area of each coral reef class. The level of coral reef damage was determined using a percentage-based calculation formula. The results indicated that in 2023, the total area of coral reefs was 113.67 ha, consisting of 51.71 ha (45.49%) of live coral reefs, 40.49 ha (35.62%) of dead coral reefs, and 21.47 ha (18.89%) of sand. Furthermore, the damage was dominated by coral fragments (28.9%) and dead coral covered by algae (23.3%), resulting in an average dead coral reef percentage of 52.2%. In conclusion, according to the standard ecological criteria, the level of coral reef damage in the waters of Maileppet Village falls into the high category.